Alkanethiol Adsorption on Platinum: Chain Length Effects on the Quality of Self-Assembled Monolayers - Floridia Addato, María Alejandra (2011)
The adsorption of butanethiol (BT), hexanethiol (HT), and dodecanethiol (DT) on Pt from ethanolic solutions has been studied by electrochemical techniques, X-ray photoelectron spectroscopy (XPS), and density functional theory (DFT) calculations. XPS data show two main S 2p components at 162.3 and 163.4 eV. The barrier properties estimated by double-layer capacitance and the blockage of the electron transfer from a redox couple in solution are markedly improved for self-assembled monolayers (SAMs) of the longer DT molecule. While the behavior of DT monolayers on Pt is comparable to that found for those grown on Au, HT and BT SAMs on Pt are more defective, are less blocking, and have a slightly lower thiolate coverage than their Au counterparts. The chain length dependent quality of these SAMs is explained based on DFT and thermodynamics calculations. It is demonstrated that a lying down (LD) surface structure dominates the stability diagram for the shorter chain thiols, while the standing up (SU) phase is more important for DT. We propose that the poor quality observed for SAMs of short chain thiolates results from an easier C?S bond scission of the thioalkyl radical in a LD configuration.